The Impact of Overclaim in Local Skincare Products on Gen Z Consumer Behavior: Forecasting Trends Among Students at Universitas Selamat Sri - Adhisty Kartika Dewi; Wahyu Sidiq Saputra (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study discusses the impact of overclaim practices in local skincare products on Gen Z consumer behavior at Universitas Selamat Sri. Overclaim, which refers to excessive claims not fully supported by scientific evidence, has been shown to reduce consumer trust and influence purchase decisions. This research uses a descriptive-verification quantitative approach to examine the effect of overclaim on trust, brand image, and purchase decisions, while also assessing the role of trust as a mediating variable. The regression analysis results indicate that overclaim significantly negatively affects Gen Z consumer behavior. Meanwhile, trust and brand image have a significant positive impact on shaping purchase decisions. The mediation test also shows that trust significantly mediates the effect of overclaim on consumer behavior. The findings highlight the importance of information transparency and evidence-based marketing practices for the local skincare industry to build consumer trust and avoid negative responses from Gen Z.